SAINS DAN TEKNOLOGI DALAM AL-QUR'AN (FENOMENA MAKROKOSMOS DAN MIKROKOSMOS) - Siti Romlah Siti Romlah (Universitas Yudharta Pasuruan, 2017)
Human thinking in the world of science had been held from the time BC to the modern times, it progresses more rapidly with technology is very advanced, though the truth of science that has been invented by man through his thinking is still a relative, therefore prone to conflicts between the one with others, some are contrary to its holy book, there are senergis with its holy book, even among science, bebil and the Qur'an. Sain is derived from the English "science" which means science among others include; 1) Astronomy; 2) political; 3) physics; 4) psychology; 5) mathematics; 6) the economy; 7) chemistry; 8) architecture; 9) sociology; 10) medicine; 11) history; 12) anthropology; 13) biology; 14) archeology; 15) agriculture and so on. While the technology is derived from the English "technology" which can be interpreted as the application of science, especially exact sciences. Of the mind and the intellect that God has given, people can explore a wide range of knowledge that exist in the universe, both macro and micro. Thus arose the various sciences.